2015
DOI: 10.1049/iet-spr.2014.0282
|View full text |Cite
|
Sign up to set email alerts
|

Admissible wavelet packet sub‐band‐based harmonic energy features for Hindi phoneme recognition

Abstract: In recent years wavelet packet (WP) transform has been used as an important speech representation tool. WP based acoustic features have found to be more effective than the short time Fourier transform (STFT) based features to capture the information of unvoiced phoneme in continuous speech. But wavelet features fail to carry the same usefulness to represent the voiced phonemes such as vowels, nasals. This paper proposes a new WP sub-band based features by taking care of harmonic information of voiced speech si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…The researchers showed that the proposed features outperform the MFCC features. Sahu et al (2014) and Biswas et al (2015), proposed a new set of acoustic features that also depend on wavelet packets called Wavelet packet based ERB (Equivalent Rectangular Bandwidth) Cepstral (WERBC). The main idea was to develop wavelet packet tree decomposition similar to the 24 sub-bands of the ERB filters (Sahu et al, 2014).…”
Section: Corresponding Author: Ihsan Al-hassani Department Of Telecomentioning
confidence: 99%
“…The researchers showed that the proposed features outperform the MFCC features. Sahu et al (2014) and Biswas et al (2015), proposed a new set of acoustic features that also depend on wavelet packets called Wavelet packet based ERB (Equivalent Rectangular Bandwidth) Cepstral (WERBC). The main idea was to develop wavelet packet tree decomposition similar to the 24 sub-bands of the ERB filters (Sahu et al, 2014).…”
Section: Corresponding Author: Ihsan Al-hassani Department Of Telecomentioning
confidence: 99%
“…al. [10] performed speech recognition using harmonic energy based features. They proposed a novice approach of new wavelet packet sub-band-based energy features.…”
Section: Related Workmentioning
confidence: 99%
“…For example, an entropy-based method for best wavelet packet basis was proposed for electroencephalogram classification [16]. The use of wavelet-based decompositions has also been applied to the development of features for speech and emotion recognition [17,18]. Other interesting proposals involve the use of evolutionary computing for the optimisation of over-complete decompositions for signal approximation [19], for the design of finite impulse response filters [20] and for the extraction frequency-domain features [21].…”
Section: Introductionmentioning
confidence: 99%